Alice Paul : equality for women - Lunardini, Christine A., 1941- (Philadelphia : Westview Press, 2013)
"Alice Paul: Equality for Women shows the dominant and unwavering role Paul played in the passage of the Nineteenth Amendment, granting the vote to American women. The dramatic details of Paul's imprisonment and solitary confinement, hunger strike, and force-feeding at the hands of the U.S. government illustrate her fierce devotion to the cause she spent her life promoting. Placed in the context of the first half of the twentieth century, Paul's story also touches on issues of progressivism and labor reform, race and class, World War I patriotism and America's emerging role as a global power, women's activism in the political sphere, and the global struggle for women's rights."--Back cover.
Becoming Alice Paul -- History strategy and politics -- Where are all the people -- A splendid year -- Taking on the Democrats -- The Democrats round two -- The war against women -- Victory and discord -- The quest for equality for women -- Epilogue.
Includes bibliographical references (pages 189-195) and index.
Keywords: Paul, Alice, -- 1885-1977.; Paul, Alice, -- 1885-1977.; Suffragists -- United States -- Biography; Women -- Suffrage -- United States -- History; Women's rights -- United States -- History; Suffragists; Women -- Suffrage; Women's rights; United States; Biographies; History; Biography; Biographies